Pembelajaran Membaca Pada Siswa Kelas Xi DenganMenggunakan Bahan Ajar Tajuk Rencana - Khairiyah, Nurul, Drs. Andi Haris Prabawa, M. Hum (2016)
The purposes of this: (1) Describing the theme in every editorial in the newspaper as Indonesian teaching materials of learning to read the course in grade XI, (2) Describing how the feasibility of an editorial in the newspaper as Indonesian teaching materials of learning to read the course in grade XI, (3) Applying learning usung teaching materials by using media editorials in the newspapers. This research used descriptive qualitative method. The data were obtained from the analysis of the students. The sources of data were the words and actions, the data in this research were collected from various newspapers. Data collection technique included observe technique and write technique. Validity was tested by triangulation of data source. Data analysis technique used the intralingual frontier model. The results of this research indicate that the themes were produced from 28 data from each editorial, which can not distinguish the theme and the title, there are 6 of data, fit for use as Indonesian teaching materials there are 24 of data, not worth 4 data as well as were equipped with the feasibility of the content and feasibility of the language. Aspects of assessment were found editorial contained in 28 data titles, the figure associated in an editorial there are 25 data problems that arise 28 Data, opinions contained in which there are 25 data, the advice there are 25 data, the conclusion 27 data, sources from various newspaper media there are 28 data. Learning to read by using teaching materials editorial in State Senior High School 1 of Gondang as interest in teaching materials used still lack, it is still difficult to distinguish between the title and the thema. By learning to read the editorial, the student is able to receive the lessons well and the school is able to receive teaching materials that have been taught by researcher.